2021
DOI: 10.3390/cancers13081957
|View full text |Cite
|
Sign up to set email alerts
|

The Targeting of MRE11 or RAD51 Sensitizes Colorectal Cancer Stem Cells to CHK1 Inhibition

Abstract: Cancer stem cells (CSCs) drive not only tumor initiation and expansion, but also therapeutic resistance and tumor relapse. Therefore, CSC eradication is required for effective cancer therapy. In preclinical models, CSCs demonstrated high capability to tolerate even extensive genotoxic stress, including replication stress, because they are endowed with a very robust DNA damage response (DDR). This favors the survival of DNA-damaged CSCs instead of their inhibition via apoptosis or senescence. The DDR represents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…RAD51, ATR and its substrate CHK1 are key molecules involved in the regulation of DNA damage repair, cell cycle checkpoint and apoptosis (Foster et al, 2012; Hjorth‐Jensen et al, 2018; Mattiello et al, 2021). HELQ is reportedly associated with these three DNA damage‐responsive factors thereby contributing to ICL repair (Anand et al, 2022; Takata et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RAD51, ATR and its substrate CHK1 are key molecules involved in the regulation of DNA damage repair, cell cycle checkpoint and apoptosis (Foster et al, 2012; Hjorth‐Jensen et al, 2018; Mattiello et al, 2021). HELQ is reportedly associated with these three DNA damage‐responsive factors thereby contributing to ICL repair (Anand et al, 2022; Takata et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…DNA damage can enhance the ability of tumor cells to be aggressive, which is associated with chromosomal instability (Morris et al, 2021). It is well-documented that the comet assay, also known as the single-cell gel electrophoresis assay, is a highly RAD51, ATR and its substrate CHK1 are key molecules involved in the regulation of DNA damage repair, cell cycle checkpoint and apoptosis (Foster et al, 2012;Hjorth-Jensen et al, 2018;Mattiello et al, 2021). HELQ is reportedly associated with these three DNA damage-responsive factors thereby contributing to ICL repair (Anand et al, 2022;Takata et al, 2013).…”
Section: Helq Regulates Dna Repair Response In Lung Cancer Cellsmentioning
confidence: 99%
“…However, some CRC stem cells display resistance to ATR or CHK1 inhibitors. In such context, one study revealed that RAD51 targeting improves the vulnerability of CRC stem cells to the CHK1/2 inhibitor prexasertib and annihilates them through triggering mitotic catastrophe by the caspase-dependent mechanism [ 131 ]. Likewise, Manic et al [ 129 ] have demonstrated that the RAD51 inhibitor B02, along with the MRE11 inhibitor mirin, selectively kills the PARP1-upregulated CRC stem cells via mitotic catastrophe without the need for exposing cells to ATR/CHK1 inhibitors [ 129 ].…”
Section: Fa Components As Promising Therapeutic Targets In Crcmentioning
confidence: 99%
“…CRC-SC with these markers depend on CHK1 activity, so LY2606368 treatment by inhibiting CHK1 impaired cell cycle checkpoint resulting in lethal replication catastrophe [145]. Interestingly, the inhibition of RAD51 (B02) or MRE11 (Mirin) was able to sensitized resistant CRC-SC to prexasertib by induction of replication stress, while others inhibitors of DDR proteins ATM, ATR, or DNA-PK were ineffective [243]. RAD51 and MRE11 are HR factors, the main pathway activated for resolving DSB during replication, and CRC-SC are tolerable to high replication stress level due to modulation of DNA damage response [156].…”
Section: Chk1 Inhibitionmentioning
confidence: 99%